2010
DOI: 10.1007/s11626-010-9327-x
|View full text |Cite
|
Sign up to set email alerts
|

Primary culture and characteristic morphologies of neurons from the cerebral ganglion of the mud crab, Scylla paramamosain

Abstract: Crustacean neurons, obtained from the cerebral ganglion of the mud crab Scylla paramamosain, were successfully cultured in vitro. They maintained typical morphological characteristics and showed better outgrowth in modified Medium 199 (M199) medium than that in Liebowitz's L-15 medium. Fetal bovine serum (FBS), muscle extracts, and hemolymph of the mud crab S. paramamosain were added as supplements. Only 20% FBS could promote neuron outgrowth, while muscle extracts and hemolymph of S. paramamosain did not impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Furthermore, it had been reported that the haemolymph of Ortosquilla oratoria (De Haan, 1844) was inhibitory in ovary cultures of Fennero penaeus chinensis (Osbeck, 1765) (cf. Tong & Miao, 1996); also, Scylla paramamosain Estampador, 1949 neuron growth was restrained in the presence of muscle extracts (Xu et al, 2010). We conclude that muscle extracts do not always play a positive role in the culture of all types of cells.…”
Section: Culture Mediamentioning
confidence: 78%
See 1 more Smart Citation
“…Furthermore, it had been reported that the haemolymph of Ortosquilla oratoria (De Haan, 1844) was inhibitory in ovary cultures of Fennero penaeus chinensis (Osbeck, 1765) (cf. Tong & Miao, 1996); also, Scylla paramamosain Estampador, 1949 neuron growth was restrained in the presence of muscle extracts (Xu et al, 2010). We conclude that muscle extracts do not always play a positive role in the culture of all types of cells.…”
Section: Culture Mediamentioning
confidence: 78%
“…However, the second kind of bipolar cell was very rare in earlier eyestalk neuron cultures. This type of cell was, for example, found in the cerebral ganglion of the mud crab (Xu et al, 2010) and in insect neuron culture (Smith & Howes, 1996;Weigel, 2005). In our studies, they had great vitality and could maintain their cell shape between 8 and 11 days.…”
Section: Cellsmentioning
confidence: 91%
“…Protocols have been developed for nervous system cells of invertebrates, particularly adult and developing insects and adult worms (Beadle 2006;Srivatsan and Peretz 1997). However, for adult decapod crustaceans, we are aware of only a few reports of nerve cell culture: Chun-Lei et al (2003) described the morphology of cultured neurons from the terminal medulla of the Chinese white shrimp Fenneropenaeus chinensis; Stepanyan et al (2004) described a protocol for olfactory neurons from the American lobster Homarus americanus, focusing on olfactory physiology; and Xu et al (2010) studied the morphology of the cells of the cerebral ganglion of the mud crab Scylla paramamosain. None of these reports described a cell-culture protocol that aimed to characterize cell types from the adult decapod crustacean nervous system in detail, as we describe here.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the characterization of invertebrate neurons and glia either in vivo or in vitro has not been explored as thoroughly as it has in vertebrates (Barres 2008). Culturing invertebrate nervous system cells may allow experimental manipulations under controlled conditions, facilitating studies on their morphology (Xu et al 2010) and functions (Stepanyan et al 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation